Agreement Between Clinical Practice and Trained Central Reading in Reading of Sacroiliac Joints on Plain Pelvic Radiographs: Results From the DESIR Cohort. Issue 9 (September 2014) - van den Berg, Rosaline; Lenczner, Grégory; Feydy, Antoine; van der Heijde, Désirée; Reijnierse, Monique; Saraux, Alain; Rahmouni, Alain; Dougados, Maxime; Claudepierre, Pascal
<x xml:space="preserve">Abstract</x> Objective To investigate the degree of agreement between local rheumatologists/radiologists and central trained readers (external standard) on the presence/absence of sacroiliitis on radiographs of the sacroiliac (SI) joints. Methods Patients with inflammatory back pain (duration ≥3 months but <3 years) suggestive of axial spondyloarthritis (SpA) were included in the Devenir des Spondylarthropathies Indifferérenciées Récentes (DESIR) cohort. Baseline radiographs of the SI joints were interpreted by 2 central readers (modified New York criteria); cases of disagreement were adjudicated by a third reader, yielding a positive or a negative result (central reading). The same radiographs were also interpreted by local radiologists/rheumatologists and were rated as "normal, " "doubtful sacroiliitis, " "obvious sacroiliitis, " or "SI joint fusion" (local reading); positive findings were defined as "at least unilateral obvious sacroiliitis, " "bilateral obvious sacroiliitis, " or "at least unilateral fusion." Agreement and misclassifications between central readers and between central reading versus local reading were calculated (kappa values). Results Interreader agreement between the central readers was moderate (κ = 0.54); 108 of 688 radiographs (15.7%) were adjudicated. According to local reading ("at least unilateral obvious sacroiliitis"), 183 of the 688 patients (26.6%) had sacroiliitis, whereas according to central reading, 145 of 688 patients (21.1%) had sacroiliitis. Agreement between local reading and central reading was also moderate (κ = 0.55); 76 of 183 patients (41.5%) with "at least unilateral obvious sacroiliitis" (positive by local reading) and 32 of 109 patients (29.4%) with "bilateral obvious sacroiliitis" or "at least unilateral fusion" (positive by local reading) were rated as "negative" by central reading, and 38 of 505 patients (7.5%) and 68 of 579 patients (11.7%), respectively, without sacroiliitis (negative by local reading) were interpreted as "positive" by central reading. Conclusion In patients with recent‐onset inflammatory back pain, both trained readers and local rheumatologists/radiologists agreed only moderately on the recognition of radiographic sacroiliitis. A significant proportion of locally recognized ankylosing spondylitis (AS) patients were not confirmed as having AS by central reading (false positive), while a small minority of patients were false negative, indicating the necessity of reevaluating the role of radiographic sacroiliitis as diagnostic criterion for axial SpA.